DEVELOPMENT OF TWO TIER MULTIPLE CHOICE DIAGNOSTIC TEST INSTRUMENT WITH CRI (CERTAINTY OF RESPONSE INDEX) ASSISTANCE TO IDENTIFY STUDENT'S MISCONCEPTION (International Conference on Social and Islamic Studies, 2022)
This study aims to determine the quality of the questions and the effectiveness of the two tier multiple choice diagnostic test assisted by CRI (certainty of response index) to identify students' misconceptions about Newton's law of motion. The type of research used is research and development (R&D) research using the Tessmer development model which consists of 4 stages, namely preliminary, self-evaluation, prototyping, and field tests. The trial subjects in this study were 30 students. The data collection instruments in this study were tests and questionnaires. The results of this study indicate that the developed diagnostic test meets the valid criteria because the result of content validity is 1.00 with a very appropriate category. The student response questionnaire has met the "achieved" criteria, because more than 50% of students gave a positive response. The results of the reliability test are 0.730 in the high category. The level of difficulty of the questions is in the range of 0.48-0.60 in the medium category. The discriminatory power of questions is in the range of > 0.2 with sufficient category. From the results of the diagnostic test, the average percentage of students who understand the concept is 45.33%, the percentage of students who experience misconceptions is 23.50%, and the percentage of students who do not understand the concept is 31.16%.